In vivo assessment of ankle stability during dynamic exercises: scoping review - Sánchez-Morilla, Sandra; Cervera-Garvi, Pablo; Ramírez-Pérez, Laura; García-Payá, Irene; Díaz-Miguel, Salvador Francisco; Ortega-Ávila, Ana Belén (MDPI, 2025)
Background: The ankle joint plays a key role in stabilizing the lower limb during interaction with ground reaction forces. Instability can result in pain, weakness, and impaired movement. Although assessing ankle stability is important, few studies examine existing in vivo methodologies for dynamic load assessment, limiting effective injury management. Objective: To identify in vivo techniques using objective measurement tools for assessing ankle stability during dynamic exercise. Methods: A scoping review was performed based on PRISMA-ScR criteria. Five databases—PubMed, PEDro, Embase, SPORTDiscus, and CDSR—were searched from inception to September 2024. Results: Out of 1678 records, 32 studies met the inclusion criteria. A total of 1142 subjects were included: 293 females (25.6%), 819 males (71.7%), and 30 unspecified (2.62%). Six categories of dynamic exercise were identified: analytical, functional, balance, stair climbing, running, and walking. The techniques used included 3D motion capture, force and pressure platforms, dynamometry, electromyography, accelerometers, pressure and speed sensors, instrumented treadmills, and inertial measurement units. Conclusions: The 3D motion capture systems (240 Hz) and the force platforms (1000 Hz) were most frequently used in functional tasks and walking. Combining these with multisegmented foot models appears optimal, though tool selection depends on study goals. This review enhances our understanding of ankle stability assessment.
Keywords: Biomecánica; Tobillos - Ejercicios terapéuticos; Ankle joint; Joint stability; Biomechanical phenomena; Technology assement; Kinematics